2014
DOI: 10.13114/mjh.201428447
|View full text |Cite
|
Sign up to set email alerts
|

Günümüzde Kadının Boşanma Deneyimleri: Akademisyen Kadınlar Üzerine Bir Araştırma

Abstract: Modernleşme çabası içinde olan günümüz toplumlarında hızlı bir değişime tanıklık edilmektedir. Yaşanan değişim ve dönüşümlerden toplum dinamiği içerisinde biçimlenmesi bakımından aile kurumu da payını alır. Ailenin birliğinin ve devamlılığının sağlanmasına yönelik baskı, bireysel istek ve arzuların daha görünür hale geldiği günümüz evliliklerinde görece azalır. Aksine günümüz toplumları, evliliğin çıkmaza girdiği zamanlarda bireylere bu çıkmazdan kurtulmalarını sağlayacak farklı yollar sunar. Boşanma da bu yol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
3
0
9
Order By: Relevance
“…When the question items in the trust and intimacy subscale are examined, it is seen that there are mostly items related to sexual life and trust to a new relationship. It has been found that the most important problem divorced women in Turkey experience in a new relationship is to build trust (Uğur, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When the question items in the trust and intimacy subscale are examined, it is seen that there are mostly items related to sexual life and trust to a new relationship. It has been found that the most important problem divorced women in Turkey experience in a new relationship is to build trust (Uğur, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Being an educated individual can be seen as a facilitating divorce for both sexes. It was observed that individuals with higher education level exhibited a more positive attitude towards divorce (Uğur, 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the process of the study, they determined that divorced individuals' differences of opinion, intervention of relatives such as parents, economic reasons, incompatibility due to differences in social environment, and physical and psychological violence were among the reasons for divorce. Uğur (2014) conducted a study on divorced academic women at Akdeniz University and tried to determine the factors affecting women's divorce decisions. As a result of the study, she emphasised that miscommunication between spouses, failure to meet the expectations of women from marriage, financial problems, unemployment of the spouse and inability to fulfil family responsibilities were influential in the decision to divorce.…”
Section: Literature Reviewmentioning
confidence: 99%